Severe pediatric asthma therapy: Dupilumab - Ferrante, Giuliana; Tenero, Laura; Piazza, Michele; Piacentini, Giorgio (Frontiers in Pediatrics, 2022)
Severe asthma is a rare disease affecting <5% of children with asthma. This group of patients accounts for about 50% of the costs of healthcare for children with asthma. Nowadays, several biological agents are available for pediatric severe asthma. One of these is dupilumab, a monoclonal antibody directed against the Interleukin (IL)-4 receptor α-subunit that acts as an antagonist against both IL-4 and IL-13. Dupilumab binds the subunit of the IL-4 receptor, at the level of the subunit shared by the IL-13 receptor, blocking the inflammatory cascade of these two cytokines and the progression of the Th2-inflammatory pathway. The efficacy and safety of dupilumab have been investigated in recently published randomized controlled trials including pediatric patients with asthma. Currently, its use in asthma is approved in adults, adolescents, and children with severe asthma with type 2 inflammation, which is inadequately controlled with high-dose inhaled corticosteroids plus another drug for maintenance treatment. Studies are warranted for the evaluation of long-term treatment with dupilumab, including steroid sparing effect and discontinuation of treatment. Further research should also be planned in order to investigate dupilumab potential in interfering with the natural history of atopic manifestations since early childhood.